Enhancing anti-tumor immune responses through combination therapies: epigenetic drugs and immune checkpoint inhibitors - Liang, Ying; Wang, Lingling; Ma, Peijun; Ju, Dongen; Zhao, Minggao; Shi, Yun (Frontiers in Immunology, 2023)
Epigenetic mechanisms are processes that affect gene expression and cellular functions without involving changes in the DNA sequence. This abnormal or unstable expression of genes regulated by epigenetics can trigger cancer and other various diseases. The immune cells involved in anti-tumor responses and the immunogenicity of tumors may also be affected by epigenomic changes. This holds significant implications for the development and application of cancer immunotherapy, epigenetic therapy, and their combined treatments in the fight against cancer. We provide an overview of recent research literature focusing on how epigenomic changes in immune cells influence [Type here] immune cell behavior and function, as well as the immunogenicity of cancer cells. And the combined utilization of epigenetic medications with immune checkpoint inhibitors that focus on immune checkpoint molecules (e.g., Programmed Death 1 (PD-1), Cytotoxic T-Lymphocyte-Associated Protein 4 (CTLA-4), T cell Immunoglobulin and Mucin Domain (TIM-3), Lymphocyte Activation Gene-3 (LAG-3)) present in immune cells and stromal cells associated with tumors. We highlight the potential of small-molecule inhibitors targeting epigenetic regulators to amplify anti-tumor immune responses. Moreover, we discuss how to leverage the intricate relationship between cancer epigenetics and cancer immunology to create treatment regimens that integrate epigenetic therapies with immunotherapies.